Extrahypothalamic oxytocin neurons drive stress-induced social vigilance and avoidance - Duque-Wilckens, Natalia; Torres, Lisette Y.; Yokoyama, Sae; Minie, Vanessa A.; Tran, Amy M.; Petkova, Stela P.; Hao, Rebecca; Ramos-Maciel, Stephanie; Rios, Roberto A.; Jackson, Kenneth; Flores-Ramirez, Francisco J.; Garcia-Carachure, Israel; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Oxytocin increases the salience of both positive and negative social contexts and it is thought that these diverse actions on behavior are mediated in part through circuit-specific action. This hypothesis is based primarily on manipulations of oxytocin receptor function, leaving open the question of whether different populations of oxytocin neurons mediate different effects on behavior. Here we inhibited oxytocin synthesis in a stress-sensitive population of oxytocin neurons specifically within the medioventral bed nucleus of the stria terminalis (BNSTmv). Oxytocin knockdown prevented social stress-induced increases in social vigilance and decreases in social approach. Viral tracing of BNSTmv oxytocin neurons revealed fibers in regions controlling defensive behaviors, including lateral hypothalamus, anterior hypothalamus, and anteromedial BNST (BNSTam). Oxytocin infusion into BNSTam in stress naïve mice increased social vigilance and reduced social approach. These results show that a population of extrahypothalamic oxytocin neurons plays a key role in controlling stress-induced social anxiety behaviors.